2008
DOI: 10.1038/eye.2008.328
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of pigment dispersion syndrome in Chinese patients

Abstract: Purpose To report clinical findings and characteristics of pigment dispersion syndrome (PDS) in Chinese patients. Methods PDS suspects with any one of the following signs: corneal endothelial pigmentation, iris transillumination defects (ITDs), pigment granule dusting on anterior iris surface, posterior iris bowing, trabecular meshwork (TM) pigmentation, and lenticular or zonular pigmentation were evaluated for PDS at the glaucoma specialty clinic at Beijing Tongren Eye Centre. Diagnosis of PDS required at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 14 publications
0
17
0
2
Order By: Relevance
“…Defects in iris transillumination are not common in our sample as well as in other noncaucasian patients 17 probably due to low incidence of light color iris compared to the dark and morphological compact iris stroma of Latin population. These findings suggest that the clinical presentation in our population can be different, and highlight the importance of a careful and complete clinical exam, including gonioscopy to enhance rate of diagnosis.…”
Section: Discussionmentioning
confidence: 49%
“…Defects in iris transillumination are not common in our sample as well as in other noncaucasian patients 17 probably due to low incidence of light color iris compared to the dark and morphological compact iris stroma of Latin population. These findings suggest that the clinical presentation in our population can be different, and highlight the importance of a careful and complete clinical exam, including gonioscopy to enhance rate of diagnosis.…”
Section: Discussionmentioning
confidence: 49%
“…A readily recognisable feature of this disease is the wide dispersion of pigment in intraocular tissues, especially on the corneal endothelium and in trabecular meshwork 31 . Our previous study in a porcine eye perfusion model suggested that iris pigment particles induced TM stress fibers, reduced TM phagocytosis, adhesion, and motility, and resulted in a significant IOP elevation 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Striking spoke-like iris transillumination defects are commonly seen in Caucasian PDS patients [1,2,4]. In this case, however, a greater content of pigment granules in melanocytes and iris stroma may have prevented such transillumination, as with most other Chinese PDS patients reported previously [5].…”
Section: Meeting Presentation Nomentioning
confidence: 80%
“…Characteristic findings of PDS include Krukenberg spindle, homogenous trabecular meshwork (TM) pigmentation, and spoke-like mid-peripheral iris transillumination defects [1][2][3][4][5]. Primary PDS usually affects bilateral eyes, although the morbidity and manifestations may be asymmetric.…”
mentioning
confidence: 97%